Association of meal and snack patterns with micronutrient intakes among Greek children and adolescents: data from the Hellenic National Nutrition and Health Survey. Issue 4 (24th April 2019) - Mitsopoulou, A.‐V.; Magriplis, E.; Dimakopoulos, I.; Karageorgou, D.; Bakogianni, I.; Micha, R.; Michas, G.; Chourdakis, M.; Ntouroupi, T.; Tsaniklidou, S.‐M.; Argyri, K.; Panagiotakos, D. B.; et al.
Abstract: Background: The present study aimed to examine how different meal and snack patterns are associated with micronutrient intakes and diet quality among a nationally representative sample of Greek children and adolescents aged 1–19 years from the cross‐sectional Hellenic National Nutrition and Health Survey ( n = 598). Methods: Meal and snack patterns were derived using 24‐h dietary recalls. Mean adequacy ratio (MAR) was used as an overall measure of diet quality. Multiple linear regression adjusted for covariates was conducted to examine associations between eating patterns, nutrient intakes and MAR. Results: Four most frequently reported eating schemes were identified including breakfast (B), lunch (L), dinner (D) and two snacks (S) (20.9%); B, L, D and 1S (16.2%); B, L, D and 3S (10.8%); and B, L and D (7.9%). Based on these schemes, the daily consumption of all main meals from the majority of the sample was highlighted. In children and adolescents aged 4–19 years, increasing snack frequency was positively associated with intakes of vitamin D, vitamin K, riboflavin, niacin, pantothenic acid, folate, magnesium, copper and selenium. An inverse association was recorded for vitamin E, vitamin B6, calcium and iron. Among children aged 1–3 years, only niacin and copper were significantly associated with number of snacks, with the group of 'B‐L‐D‐2S' presenting the highest intake. As for the overall diet quality, among all participants, there was no significant association of MAR with the type of meal and snack pattern, and thus the snack frequency. Conclusions: Snacking behaviour is a common practice among children and adolescents. Modifying current snack foods with nutrient‐rich choices could lead to an improvement of their diet's nutritional quality.